Infección del tracto urinario como factor de riesgo de parto pretérmino en el servicio de Gineco-Obstetricia del Hospital Teófilo Dávila. - Martínez Guiacha, Guliana Pierina (2016)
Urinary tract infections in pregnant women are a global health problem, which have become increasingly important in recent years, being one of the major causes, in some countries the main cause, of both threatened and established preterm labor in pregnant women who suffer from these diseases. The overall objective of this research lies in the importance of analyzing urinary tract infections as a cause of preterm birth, while the specific objectives are to identify how many patients present threatened preterm labor and established preterm labour, establish the socioeconomic characteristics of each patient, determine the symptoms along with the most common causative germ, and analyze the therapeutic management provided to each pregnant woman. This descriptive – retrospective study was carried out based on 111 patients that met the inclusion criteria's requirements, whose information was obtained by means of a pre-prepared data collection sheet, which was completed using data taken from the medical records of patients who were treated at the Teófilo Dávila Hospital during the period 2014-2015. The study obtained the following results: of the 321 patients who presented urinary tract infections, 210 had threatened preterm labor in its early stage, the rest 111 ended up with established preterm labor; in regards to the socio-economic conditions, the lower-middle class predominated with 35 patients; the germ most frequently isolated was E.coli found in 92 patients; the symptom of greatest frequency was dysuria with 40 patients; 69 received inpatient treatment with cefazolin while 42 received treatment with ceftriaxone. Concluding that urinary tract infections are a major cause of both threatened and established preterm labor in the Teófilo Dávila Hospital. Keywords: Urinary Tract Infection, Threatened Preterm Labor, Established Preterm Labor